2009
DOI: 10.1227/01.neu.0000338427.44471.1d
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Meningioma Surgery in Elderly Patients With Paraplegia or Severe Paraparesis

Abstract: OBJECTIVE In a multicenter study, 102 patients aged 70 years or older with paraplegia or severe paraparesis, and who underwent operation for spinal meningiomas, are presented to correlate surgery and outcome and to determine the most influential factors that affected this outcome. METHODS Five French neurosurgical centers participated in this retrospective study between 1990 and 2007. Pre- and postoperative neurological statu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(54 citation statements)
references
References 30 publications
2
50
1
Order By: Relevance
“…Gerszten et al [9] reported radiographic control of mainly recurrent meningiomas with radiosurgery; however, more studies are needed with longer follow-up periods. Advanced age does not seem to contraindicate surgery, even in patients with severe preoperative neurological deficits the quality of life can be improved in most cases [10]. For ventrally located spinal meningiomas, the transthoracic approach has been used.…”
Section: Discussionmentioning
confidence: 99%
“…Gerszten et al [9] reported radiographic control of mainly recurrent meningiomas with radiosurgery; however, more studies are needed with longer follow-up periods. Advanced age does not seem to contraindicate surgery, even in patients with severe preoperative neurological deficits the quality of life can be improved in most cases [10]. For ventrally located spinal meningiomas, the transthoracic approach has been used.…”
Section: Discussionmentioning
confidence: 99%
“…6 The reports discussing a subset of spinal meningiomas were excluded as well. 11,28,37,46,49 The summary of these studies are tabulated (see Table 5). …”
Section: Literature Reviewmentioning
confidence: 99%
“…Posterior spinal approaches provide for adequate exposure of the dorsal spinal cord and posteriorly situated lesions, with the potential for lateral extension by transpedicular or costotranversectomy approaches for larger lesions or lesions with more ventral extension (50). However, doing so is often at the expense of segmental spinal stability requiring instrumented fusion (28).…”
Section: Surgical Approachesmentioning
confidence: 99%